Developing the use of formulaic language for study abroad: a targeted instructional intervention. Issue 4 (4th July 2022) - Wang, Jiayi; Halenko, Nicola
ABSTRACT: This study investigates the immediate and sustained effects of a pre-departure study abroad training on the oral production of L2 Chinese formulaic language across a range of social and transactional interactions. Eighteen upper-intermediate learners of Chinese were assigned to either an instructed or non-instructed group to determine the efficacy of instruction designed to enhance their study abroad year in China and beyond. A three-stage pre-post-delayed longitudinal experimental design was adopted to examine instructional effects over an academic year, elicited by means of a computerised oral task (COT). The assessment was based on quantitative appropriateness ratings and a qualitative analysis of the output. Results show that the instructed group outperformed the control group immediately after the pre-study abroad (pre-SA) instruction, as well as after the year abroad. The significant difference between the two groups, however, decreased after the period abroad as the control group also showed significant improvement without the pre-SA instruction. Nevertheless, the sustained effect of the instruction enabled the experimental group to retain their competitive edge, even after a year in the target language country. The findings demonstrate the longitudinal benefits of pre-SA instruction.